(untitled) (Swiss Medical Weekly, 2025)
Bacillus cereus, a gram-positive, rod-shaped bacterium known for both its environmental resilience and its pathogenic potential, has been increasingly recognised as a serious health threat outside the traditional contexts of food poisoning. This narrative review, anchored by a detailed case study, highlights the pathogen’s role in rare but severe infections like endocarditis, especially among intravenous drug users, who are particularly vulnerable, among other identified risk factors. The case of a 62-year-old female with a history of intravenous cocaine use who developed Bacillus cereus endocarditis underscores the complexities of diagnosing and managing such infections. Despite the challenges posed by the patient’s adverse reactions to vancomycin, the mainstay treatment, successful management was achieved through persistent administration adjusted for tolerance and side effects. This review meticulously compiles all known cases of Bacillus cereus endocarditis from the past decades, beginning with the first identified case fifty years ago in 1974. It provides a thorough analysis, identifying various risk factors and outlining the evolution of treatment protocols. This comprehensive approach not only enhances understanding of the pathogen’s clinical impact but also clarifies the progression of therapeutic strategies, highlighting the individual adaptations necessary to address this challenging infection effectively.